KONSEP KONVERGENSI IFRS DI INDONESIA Apakah berdampak dengan Kualitas Laba dan Prilaku Manajer dalam melakukan Perataan Laba (suatu telahaan Kualitatif Fenomenologi) - Anis Rachma Utary (Prodi Ilmu Administrasi Negara, 2015)
This study is the qualitative one by Fenology approach which discribes deeper action of the process of IFRS which welknown as the standard of international accounting finance. There are many effects of it will appear by convergency which one of is the profit quality from the finance report and the behaviour of the manager in manipulation of the profit or the smoother word as known the profit average. The study by qualitative approah uses some informants as the human resource in the issue of this convergency. The informants used among are academic level, students, the those who are company managers and the finance managers. After introducing IFRS the level of the profit management becomes lower, the relevance of the value higher the and the aquasition of the loss more exact time, compared with before the transisition PSAK GAAP. Then even the adoption of the IFRS in the first year is worse which is caused by the transisition cost to the IFRS. But the quality of the company finance will improve in the following period